(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
Grief is a common human experience that is frequently explored in literary texts through characters’ responses to loss. This study examines the depiction of grief in Train Dreams by Denis Johnson through Kübler-Ross’s Five Stages of Grief model. Using a qualitative approach and a close reading technique, this study analyzes the passages that depict Grainier’s emotional reactions after losing his wife and daughter. The findings indicate that Grainier’s grief is mainly depicted through such stages of the process as denial, bargaining, depression, and acceptance. His grief is further intensified by his long-term isolation and previous experience of separation. The study also demonstrates that grief is initially articulated through self-directed speech, memories, and private reflection before developing into social articulation during Grainier’s conversation with Claire. These findings demonstrate that Train Dreams depicts grief as a sequence of psychological stages and a gradual narrative process through private experiences of loss that becomes expressible over time. The study contributes to the literary academic of grief by extending the Kübler-Ross model application beyond identifying emotional stages to show how grief develops and is progressively articulated within literary work.